2014
DOI: 10.1007/s11426-014-5208-6
|View full text |Cite
|
Sign up to set email alerts
|

In-situ green synthesis of highly active GSH-capped Pt-Au-Ag-hybrid nanoclusters

Abstract: Recently much attention has been paid to the application of metal hybrid nanoparticles in industrial catalytic fields because of their super-efficient catalytic activity and attractive properties. We explored a novel strategy to prepare GSH-capped Pt-Au-Ag-hybrid nanoclusters through the synergistic effect between ascorbic acid (VC) and glutathione (GSH) with chloroplatinic acid, chloroauric acid, and silver nitrate as precursors. The potential utilization of as-prepared GSH-capped Pt-Au-Aghybrid nanoclusters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…The full-range X-ray photoelectron spectrometry (XPS) analysis (Figure B) showed five evident peaks at 84.0, 163.0, 285.0, 400.1, and 530.6 eV, which could be attributed to Au 4f, S 2p, C 1s, N 1s, and O 1s, respectively. The Au 4f core-level spectra are shown in Figure C, with the peaks at 84.0 and 87.6 eV corresponding to Au 4f 7/2 and Au 4f 5/2 , respectively . The spectrum of S 2p (Figure D) revealed the existence of S 2 2– , S 2– , and S 0 /S n 2– , demonstrating the Au–S bond on the surface of Au NCs .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The full-range X-ray photoelectron spectrometry (XPS) analysis (Figure B) showed five evident peaks at 84.0, 163.0, 285.0, 400.1, and 530.6 eV, which could be attributed to Au 4f, S 2p, C 1s, N 1s, and O 1s, respectively. The Au 4f core-level spectra are shown in Figure C, with the peaks at 84.0 and 87.6 eV corresponding to Au 4f 7/2 and Au 4f 5/2 , respectively . The spectrum of S 2p (Figure D) revealed the existence of S 2 2– , S 2– , and S 0 /S n 2– , demonstrating the Au–S bond on the surface of Au NCs .…”
Section: Resultsmentioning
confidence: 96%
“…The Au 4f core-level spectra are shown in Figure 2C, with the peaks at 84.0 and 87.6 eV corresponding to Au 4f 7/2 and Au 4f 5/2 , respectively. 51 The spectrum of S 2p (Figure 2D) revealed the existence of S 2 2− , S 2− , and S 0 /S n 2− , 52 demonstrating the Au−S bond on the surface of Au NCs. 39 The peaks of C 1s (Figure 2E 2F) .…”
Section: Acs Applied Nano Materialsmentioning
confidence: 97%
“…These NPs (PSs) absorb the light in the form of a photon and transfer it to local oxygen containing molecules that release various kinds of ROS and 1 O 2 . [121][122][123][124] Recently NT combined inorganic materials with organic macromolecules as PSs to achieve their synergistic effects in PDT. 4).…”
Section: Photodynamic Treatmentmentioning
confidence: 99%
“…gold, 107,108 silver, 109 zinc, 110,111 carbon fibers and complexes, 112,113 platinum, 114,115 titanium, 116 iron, 117,118 cerium, 119 ruthenium, 120 etc., and/or their hybrid clusters. [121][122][123][124] Recently NT combined inorganic materials with organic macromolecules as PSs to achieve their synergistic effects in PDT. 125,126 Over the last few decades, the potential of nano-TiO 2 as an inorganic PS for PDT has been extensively explored.…”
Section: Photodynamic Treatmentmentioning
confidence: 99%
“…Qiu Jian Ding et al reported that a green method employed for synthesizing peptide-templated nanoclusters without requiring strong reducing agents [13]. Wang Xue Mei reported in situ green synthesis of highly active GSH-capped Pt-Au-Ag-hybrid nanoclusters [14]. Lina Zhao et al synthesized a typical peptide coated AuNC [15].…”
Section: Introductionmentioning
confidence: 99%